Improvement of biomass properties by pretreatment with ionic liquids for bioconversion process - Weerachanchai, Piyarat (2013)
Cassava pulp residue and rice straw were used as a precursor for pretreatment with ionic liquids to study the effects of pretreatment conditions on product yield and properties. Cassava pulp residue is a potential biomass in the bioconversion process due to it requiring mild pretreatment conditions while providing a high sugar conversion. The maximum sugar conversion and lignin extraction are attained from pretreatment of biomasses with particle size of <38 μm and ionic liquid of 1-Ethyl-3-methylimidazolium acetate at 120 °C for 24 h. The effectiveness of ionic liquid for biomass pretreatment process follows the sequence: 1-Ethyl-3-methylimidazolium acetate > 1-Ethyl-3-methylimidazolium diethyl phosphate > 1,3-Dimethylimidazolium methyl sulfate. The increase of pretreatment temperature from 25 to 120 °C and decrease of biomass particle size renders higher sugar conversion, lignin extraction and lower crystallinity index. However, pretreatment at temperatures higher than 120 °C shows a sharp decline of regenerated biomass yield, sugar conversion and lignin extraction and giving higher crystallinity index at pretreatment temperature of 180 °C.